The great treehouse war - Graff, Lisa (Lisa Colleen) 1981- (New York, NY Philomel Books, 2017)
Fifth-grader Winnie, with notes from her friends, writes of turning her treehouse into an embassy after her newly-divorced parents become unreasonable, where she is joined by nine others with complaints.
School Library Journal, April 2017
Booklist, April 2017
Horn Book, July 2017
Bulletin (Center for Children's books), May 2017
Kirkus Review, March 2017
Publishers Weekly Annex, May 2017
Keywords: Interpersonal relations -- Fiction; Parents -- Fiction; Divorce -- Fiction; Friendship -- Fiction; Tree houses -- Fiction; Humorous fiction